2016
DOI: 10.1080/07391102.2016.1262279
|View full text |Cite
|
Sign up to set email alerts
|

New potential inhibitors of mTOR: a computational investigation integrating molecular docking, virtual screening and molecular dynamics simulation

Abstract: The mTOR (mammalian or mechanistic Target Of Rapamycin), a complex metabolic pathway that involves multiple steps and regulators, is a major human metabolic pathway responsible for cell growth control in response to multiple factors and that is dysregulated in various types of cancer. The classical inhibition of the mTOR pathway is performed by rapamycin and its analogs (rapalogs). Considering that rapamycin binds to an allosteric site and performs a crucial role in the inhibition of the mTOR complex without c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…This site is located in a deep cleft and hydrophobic pocket behind the binding domain. Our control docking is also validated with a similar binding site which has been reported earlier [ 55 ]. It is suggested that the shared macrolide structure between rapamycin and everolimus permits interaction with FKBP5, subsequently to be selective to inhibit mTORC1 over mTORC2 [ 56 ].…”
Section: Resultssupporting
confidence: 55%
“…This site is located in a deep cleft and hydrophobic pocket behind the binding domain. Our control docking is also validated with a similar binding site which has been reported earlier [ 55 ]. It is suggested that the shared macrolide structure between rapamycin and everolimus permits interaction with FKBP5, subsequently to be selective to inhibit mTORC1 over mTORC2 [ 56 ].…”
Section: Resultssupporting
confidence: 55%
“…As shown in Figure 1 , the docked conformation predicted for rapamycin (in violet) is spatially close to the crystallographic structure pose (in yellow) with an optimal RMSD value of 1.44 Å. In addition, as shown in Table 1 , the best binding energy calculated for rapamycin (−8.6 kcal·mol) was in good agreement with the literature data (−8.4 kcal·mol) [ 26 ]. These findings indicate a high-level of the feasibility in our protein-ligand docking procedure, which was able to reproduce the binding pose of the cocrystallized ligand deposited in the PDB ID: 4DRI.…”
Section: Resultssupporting
confidence: 81%
“…An important signaling pathway called PI3K/Akt/mTOR pathway is believed to be the most frequently dysregulated pathway in various cancers [Samuels et al, 2004;Engelman et al, 2006;Liu et al, 2009] and therefore, the key proteins of this pathway is often targeted in multitude of cancer types [Morgensztern and McLeod, 2005;Shuttleworth et al, 2011;Jamal et al, 2014;Polivka and Janku, 2014;Porta et al, 2014;Rehan et al, 2014;Rehan, 2015]. One of such key proteins of this pathway is mammalian target of rapamycin (mTOR), which is widely exploited as a drug target for anti-cancer therapy [Helena et al, 2012;Kist and Caceres, 2016;Wang et al, 2016].…”
mentioning
confidence: 99%